Bibliometrical Analysis: Research Trend in Course and Training for Arabic Language - Musyafa’ah, Lili; Jihan, Farah Nur; Kaserero, Subira; Aini, Sarah Hajar; Ramadani, Ghina (Universitas Negeri Padang, 2025)
Abstracts This article presents a bibliometric analysis of literature related to Arabic language courses and skills training, with the aim of understanding trends, patterns, and developments in research in this field from 1943 to 2024. The method of bibliometric analysis is used to identify topics that are most studied, as well as journalists and authors who are influential in the context of Arabic language learning. The data was obtained from the Publish or Perish and Google Scholar databases, which produced 136 papers consisting of journal articles, conference proceedings, and books. Furthermore, the research reveals the need to develop training programmes that are more effective and relevant to the needs of the community. These findings provide valuable insights for educational practitioners and policymakers in designing curricula that fit the developments of the times. Thus, this article not only describes research developments in the field of Arabic language courses and training, but also identifies gaps in existing literature, as well as provides recommendations for future research and educational practice.